Pelvic Floor Dysfunction Symptoms, Causes, and Treatment - Pang, Ran (IntechOpen, 2022)
Pelvic floor disorders (PFDs) refer to a group of conditions, such as urinary incontinence, fecal incontinence, and pelvic organ prolapse, due to weakened or injured pelvic muscles and connective tissues. People with PFDs face several social, mental, and physical health effects due to the bothersome symptoms. In this book, experts and researchers from different countries present the latest evidence in diagnosis and treatment of PFDs. Chapters cover such topics as pelvic floor muscle activity, PFDs and pregnancy and childbirth, non-invasive therapy, dysfunctional voiding in children, and much more.